Study of wave signatures observed in thermospheric airglow imaging over the dip equatorial region - Sau, Sukanta; Narayanan, V. Lakshmi; Gurubaran, S.; Emperumal, K. (My University, 2018)
The observational data on OI 630 nm thermospheric nightglow from the Indian dip equatorial station, Tirunelveli (8.7 N, 77.8 E geographic, 1.6 N dip latitude) obtained between January 2013 and January 2015 using an All-Sky Airglow Imager (ASAI) are utilized in this work to examine the presence of gravity waves in the thermosphere. Two types of wave signatures were observed: (1) quasi-periodic waves consisting of alternating crests and troughs and (2) single bands of enhanced intensity (SBEI). The phase speed, wavelength and time period of the quasi-periodic waves were in the range of 70–160 m/s, 130–575 km and 25–75 min, respectively, while the phase speed and scale size of the SBEI features were found to be in the range of 150–250 m/s and 230–470 km, respectively. During equinoxes, quasi-periodic waves propagated towards north-northwest direction, while during winter they were observed to propagate towards northwest, south-southwest and southeast directions.
Keywords: MSTID; Thermospheric airglow; Thermospheric gravity waves; Low latitude ionosphere